The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1017/thg.2018.12
|View full text |Cite
|
Sign up to set email alerts
|

Comment on ‘Large-Scale Cognitive GWAS Meta-Analysis Reveals Tissue-Specific Neural Expression and Potential Nootropic Drug Targets’ by Lam et al.

Abstract: Intelligence and educational attainment are strongly genetically correlated. This relationship can be exploited by Multi-Trait Analysis of GWAS (MTAG) to add power to Genome-wide Association Studies (GWAS) of intelligence. MTAG allows the user to meta-analyze GWASs of different phenotypes, based on their genetic correlations, to identify association's specific to the trait of choice. An MTAG analysis using GWAS data sets on intelligence and education was conducted by Lam et al. (2017). Lam et al. (2017) report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 26 publications
2
20
3
Order By: Relevance
“…Of note are the variables of autism and schizophrenia. As found in previous studies 8,49,51,65,66 schizophrenia showed a small positive genetic correlation with EA (rg=0.06, SE=0.02, P=1.15 × 10 −3 ) whereas, in the present study, income showed a negative genetic correlation with schizophrenia (rg=−0.14, SE=0.02, P=6.49×10 −9 ); the difference between these two genetic correlations was significant (P=6.57×10 −11 ). Autism also showed a positive genetic correlation with EA (rg=0.27, SE = 0.03, P=1.10×10 −15 ) as found previously, 8,51,67 whereas income showed no detectable genetic correlation with autism (rg=0.04, SE=0.05, P=0.37), and this difference was again significant (P=1.17×10 −11 ).…”
Section: Genetic Correlationssupporting
confidence: 86%
“…Of note are the variables of autism and schizophrenia. As found in previous studies 8,49,51,65,66 schizophrenia showed a small positive genetic correlation with EA (rg=0.06, SE=0.02, P=1.15 × 10 −3 ) whereas, in the present study, income showed a negative genetic correlation with schizophrenia (rg=−0.14, SE=0.02, P=6.49×10 −9 ); the difference between these two genetic correlations was significant (P=6.57×10 −11 ). Autism also showed a positive genetic correlation with EA (rg=0.27, SE = 0.03, P=1.10×10 −15 ) as found previously, 8,51,67 whereas income showed no detectable genetic correlation with autism (rg=0.04, SE=0.05, P=0.37), and this difference was again significant (P=1.17×10 −11 ).…”
Section: Genetic Correlationssupporting
confidence: 86%
“…Lam et al (2018) also state ‘our leave-one-out analyses (Figure 3 in Lam et al ((2017)) demonstrate that prediction of held-out samples, phenotyped for cognitive ability, are better for MTAG than for either GWAS COG or GWAS EDU alone. This finding supports our interpretation that MTAG is boosting polygenic signal for cognition, and does not support the conclusion of Hill (2018) that the MTAG polygenic signal is ‘indistinguishable from that of education’’. The phrase ‘indistinguishable from that of education’ is attributed to Hill (2018) but it is not found in the manuscript of Hill (2018).…”
contrasting
confidence: 79%
“…The third piece of evidence Lam et al (2018) use to show that their MTAG analysis is more similar to cognitive ability than to education, is to claim the magnitude of the genetic correlations with education were reported inaccurately by Hill (2018). In their rebuttal, Lam et al (2018) write that ‘Hill (2018) elides the fact that the calculation method employed by LD score regression is known to sometimes produce values for r g >1, if the variables are so highly similar as to be self-same (Walters, 2016)’. However, Hill (2018) states in his Table 1, Figure 1, and in the publically available scripts used by Hill (2018) to perform his analyses that genetic correlations of greater than 1 are being treated as 1.…”
mentioning
confidence: 99%
See 2 more Smart Citations